# Isolate y from equation: `e^y=(1+x^2)*C-1`

### 2 Answers | Add Yours

It is given that `e^y=(1+x^2)*C-1`

To isolate y, take the natural logarithm of both the sides.

=> `ln(e^y) = ln((1 + x^2)*C - 1)`

Use the property `log a^b = b*log a`

=> `y*ln e = ln((1 + x^2)*C - 1)`

The base of natural logarithm is e and `log_b b = 1`

=> `y = ln((1 + x^2)*C - 1)`

**The required expression for y is **`y = ln((1 + x^2)*C - 1)`

Do you want to express something like, y = function of x, then the solution is given below:

Given expression is:

e^y = (1+x^2)C - 1

Take natural log(log with base e) on both sides:

log [e^y] = log [ (1+x^2 )*C - 1]

=> y = log [ (1+x^2 )*C - 1]

Which is in the desired form.